Changes in the incidence of acute bacterial meningitis caused by Streptococcus pneumoniae and the implications of serotype replacement in children in Colombia after mass vaccination with PCV10 - Farfán-Albarracín, Juan David; Camacho-Moreno, Germán; Leal, Aura Lucia; Patiño, Jaime; Coronell, Wilfrido; Gutiérrez, Iván Felipe; Beltrán, Sandra; Álvarez-Olmos, Martha I.; Mariño, Cristina; Barrero, Rocio; Rojas, Juan Pablo; Espinosa, Fabio; et al. (Frontiers in Pediatrics, 2022)
Acute bacterial meningitis(ABM) is a public health problem. The disease has reemerged after the introduction of pneumococcal conjugate vaccines(PCVs) due to an increase in serotypes that are not covered. The objective was to determine the changes in the disease incidence before and after the introduction of the 10-valent vaccine(PCV10) in Colombia. Methods:This multicenter study was conducted in 17 hospitals in Colombia. Data were collected from January 2008 to December 2019 in 10 hospitals in Bogotá and from January 2017 to December 2019 in seven hospitals in Cali, Medellín and Cartagena. The data were grouped into three periods: 2008-2011, 2012-2015 and 2016-2019. Results:Of the 706 cases of invasive pneumococcal disease, 81(11.4%) corresponded to meningitis. The relative incidence in Bogotá in the first period was 0.6 x100,000 patients ≤ 5years, decreased to 0.4x100,000 patients ≤ 5years in the second period and increased in the third period to 0.7x100,000 patients≤5years. Serotypes covered by PCV10 decreased from 75% to 9.1%, with Spn19A(31.8%) and Spn34(13.6%) emerging in the third period. Increased resistance to penicillin(13% to 37%) and to ceftriaxone(5.9% to 16%) was due to the emergence of multidrug-resistant Spn19A. The total mortality rate was 23.5% and increased from 12% to 33%. Conclusions:ABM due to pneumococcus has high morbidity and mortality rates. Reemergence of the disease has been observed due to the inclusion of polymerase chain reaction(PCR) for diagnosis and replacement of circulating serotypes after the introduction of PCV10, with an increase in Spn19A, which causes death and exhibits antimicrobial resistance. Continued surveillance is needed.